(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Dalimunthe NP, Alikodra HS, Iskandar E, Atmoko SSU. 2021. The activity budgets of captive orangutan (Pongo pygmaeus) in two different Indonesian zoos. Biodiversitas 22: 1912-1919. In nature, orangutans spent most of the activity budgets for foraging. It is presumed that orangutan in captivity carries out different activities. This study aimed to investigate the activity of Bornean Orangutan (Pongo pygmaeus) in different zoos with different types of cage according to their design, enrichments, and diets. It was conducted at two different Indonesian zoos, namely Ragunan Zoo (TMR) and Taman Safari Indonesia (TSI). The study used a total of 11 orangutans. From each zoo, orangutan individuals from each zoo and each age and sex class (adult male, adult female, and juvenile/juvenile) were used in the present study. The activity budgets were compared between age-sexual classes, cage types, and weekday-holiday categories. Environmental enrichment analysis was also used. The total observation time in this study for each individual was 4,500 minutes. The adult male had more resting activity than other groups, while the juvenile group showed a higher percentage of social, moving, and feeding activities. It was also observed that there were different activity budgets between individuals in a separate cage and week-holiday groups. Overall, it was assumed that the difference in orangutan activity budgets was influenced by cage types, individual arrangements, and environmental enrichment. Meanwhile, a juvenile showed a higher percentage of enrichment using. Enrichment was influenced by cage type and individual arrangement.